Persönlichkeitsschutz und Presseberichterstattung im deutschen und italienischen Recht Unter besonderer Berücksichtigung der materiellrechtlichen Abwägung und richterrechtlichen Bildung von Verhältnismäßigkeitskriterien - Schmitt-Mücke, Caroline (Schriften zum Äußerungs- und Medienrecht, 2023)
The dissertation deals with the tension between subjective protection of personality and freedom of the press in German and Italian law. In addition to a comprehensive review of both legal systems, the thesis compares the respective national solutions and examines their actuality and practicability in the current media reality. To this end, the author primarily examines the individual case-related balancing practice, analyses the respective judicial formation of balancing criteria also with regard to the influence and the respective consideration of the case law of the ECJ and ECtHR and evaluates the necessity and degree of harmonisation of the area of tension.